The effects of football match congestion in an international tournament on hip adductor squeeze strength and pain in elite youth players - Wollin, M.; Pizzari, T.; Spagnolo, K.; Welvaert, M.; Thorborg, K. (Journal of Sports Sciences, 2018)
The purpose of this study was to investigate the effect of a congested international tournament match schedule on adductor strength and pain in elite youth football players. Twenty-two male players (age: 15.53 ± 0.48 years, height: 174.87 ± 7.59 cm, weight: 67.45 ± 7.40 kg) were included. The 5-second adductor squeeze strength was captured daily using a hand-held dynamometer during a 7-game international tournament. Pain during the squeeze test was recorded using numerical pain ratings (0-10) to quantify groin pain. Sessional rate of perceived exertion (sRPE) was collected during the tournament. Adductor strength changed significantly during the tournament in relation to time (F(14,294.94) = 1.89, p = 0.027) and cumulative sRPE (F(1,314) = 5.59, p = 0.019). Cumulative sRPE displayed a negative relationship with strength (B = -0.008, SE = 0.0032, 95%CI = -0.014,-0.002). The results indicate that for every 100 match sRPE arbitrary units the squeeze peak force reduced by 0.8N. Sixteen (72.7%) players demonstrated clinically meaningful strength reductions (>15%) during the tournament. Match congestion impacts on hip adductor squeeze strength in male youth football players. A negative relationship between match sRPE and adductor strength exists. Player monitoring involving the 5-second adductor squeeze test can be captured effectively and is suitable to include as part of secondary injury prevention during or immediately after a congested tournament.